Analysis of the Efficiency of State-Owned Assets Management Based on Performance Indicators in Supporting Economic Growth (SDG 8) - Gloria Kartika Simbolon; Aulia Aulia; Maya Macia Sari (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
This study aims to analyze the influence of State-Owned Assets (BMN) management efficiency based on performance indicators on its contribution to supporting Sustainable Development Goal (SDG) 8, particularly the aspect of employment absorption. Using a quantitative approach with panel data from 13 Ministries/Agencies for the 2021–2024 period, this research examines the influence of four main performance indicators—productivity and accountability (X1), regulatory compliance (X2), supervision effectiveness (X3), and BMN administration (X4)—on employment absorption (Y) as a proxy for SDG 8. The results of panel data regression analysis with the Fixed Effect model show that only the productivity and accountability variable (X1) has a positive and significant partial effect. However, all four indicators simultaneously have a significant influence and can explain 68.98% of the variation in employment absorption. These findings confirm that a performance-based BMN management approach, especially one focused on optimizing the economic value of assets, makes a tangible contribution to driving inclusive economic growth and job creation, in line with the SDG 8 agenda.